Evaluation of a biopsychosocial education resource for mild traumatic brain injury: a mixed method exploratory study - Faulkner, Josh W.; Callagher, Elise; Snell, Deborah; Nielsen, Kristopher; Cairncross, Molly; Theadom, Alice (Frontiers in Neurology, 2024)
Introduction Education is strongly advocated as a key component of treatment for mild traumatic brain injury (mTBI) in clinical guidelines. However, there is mixed evidence on the benefit of education. This study aimed to evaluate a new education resource for mTBI. CLARITY is a freely available animated video based on a biopsychosocial conceptualization of mTBI, explaining the complex psychological, environmental and biological mechanisms behind symptoms and recovery.1 Methods 24 adults with a history of mTBI participated in this mixed method study to examine prior experience of mTBI education and to evaluate CLARITY. Following viewing of the education video participants’ were invited to engage in a semi-structured interview and to share their perceptions of it via an online anonymous questionnaire. Results Thematic analysis of semi-structured interviews revealed one overarching theme: education is the foundation of recovery. Participants emphasised the critical role of coherent education in facilitating understanding, engagement in rehabilitation, and positive expectations during recovery. However, the first subtheme was that existing foundations are weak. Participants’ previous education was often limited in scope, inconsistent, and delivered in inaccessible ways. The second subtheme was that new foundations are stronger. Participants responded positively to CLARITY, highlighting its explanatory biopsychosocial approach, focus on mental health factors and accessible delivery methods as key strengths. Questionnaire responses revealed favourable endorsement of CLARITY’s utility, comprehensibility and accessibility. Discussion Recommendations for minor refinements to CLARITY were provided and made, as well as for its use in health care services.